Associação entre suporte social e atividade física no lazer em adultos - Silva, Inácio Crochemore Mohnsam da (2010)
Objective: To explore the association between social support from family and friends and the practice of leisure-time physical activity (PA) in adults (≥20 years old). Methodology: Population-based, cross-sectional study, conducted in Pelotas/RS. The sampling process occurred in multiple stages. Leisure-time PA was measured with the long version of the International Physical Activity Questionnaire. Those who reported an PA practice of ≥150 minutes on the week before the interview were considered active. Specific estimates for walking and moderate and vigorous PA (MVPA) were performed. Social support was collected with a Social Support Scale for PA and different exposure variables were built according to the sources of support (family or friends), levels of exposure and type of PA practice. The developed analysis was stratified by sex. For the association between social support and PA a Poisson regression was used with robust adjustment of variance. Complementary analysis stratified the sample in two age groups (20-39 years old and ≥40 years old). Results: There was a strong association between social support and leisure-time PA in adults (RP≥ 2,0). Considering the walks, prevalence ratios between men were lower than the ones between women. Restricting the analysis to MVPA, the greatest risk measures belonged to male. Comparing the studied sources of social support, the magnitude of the association was always greater with the support from friends in relation to the social support from family, independent of the PA type. However, the effect on the individuals was even more important when the social support was provided simultaneously by family and friends. Conclusion: It stands out the importance of different types of support for leisure-time PA practice. It is believed that the interventions based on the mobilization of individuals and their social environment will have greater effectiveness power in the promotion of active lifestyles.